Eksplorasi Sistem Adat Desa Penglipuran Sebagai Inspirasi Pendidikan Kontekstual di Era Modern - Ardi Pranoto, Reno; aprilianti, putri; Auliatul Faizah, Vina; Aurastanarif Syahnar, Alhimmah; Muamar , Muamar (Jurnal Cahaya Edukasi, 2025)
This study examines the customary system of Penglipuran Village in Bali as a source of inspiration for the development of contextual education in the modern era. Penglipuran Village, which is famous for its unique culture and local wisdom, holds social and cultural values that can be applied in learning to shape children's character and identity in an increasingly global world. This study uses a qualitative approach with observation and interview methods with community leaders and educators in the village. The results of the study indicate that the customary system that prioritizes mutual cooperation, respect for nature, and respect for tradition can be integrated into the education curriculum to introduce educational concepts that are more relevant to real life. In the context of contextual education, the application of these values is expected to create more meaningful learning, connect students with local culture, and prepare them to become wise and responsible individuals amidst the rapid development of the era.